2018
DOI: 10.1007/s11157-018-9462-5
|View full text |Cite
|
Sign up to set email alerts
|

Composting leachate: characterization, treatment, and future perspectives

Abstract: The increasing production of waste has led to one of the major environmental challenges of today: waste management. A solution to this problem is the composting of organic wastes. While the composting process transforms organic wastes into biologically stable compost, large amounts of highly contaminated leachates that present a direct risk to the environment are also produced. First off, this review discusses the origin and nature of contaminants found in composting leachates. In a general perspective, compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…Lim et al [37] observed a decrease of biogas yield for organic loads that were over 4 kg COD /m 3 d. On the contrary, other works identified much higher OLR values as the most profitable for biogas production [10]. The literature reports are quite different also in regards to the methane content of biogas originating from the anaerobic digestion of composting leachate [36]. These differences, probably, depend on the reactor type and on the characteristics of treated leachate and highlight how the digestion of compost leachate is not well clarified yet.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lim et al [37] observed a decrease of biogas yield for organic loads that were over 4 kg COD /m 3 d. On the contrary, other works identified much higher OLR values as the most profitable for biogas production [10]. The literature reports are quite different also in regards to the methane content of biogas originating from the anaerobic digestion of composting leachate [36]. These differences, probably, depend on the reactor type and on the characteristics of treated leachate and highlight how the digestion of compost leachate is not well clarified yet.…”
Section: Introductionmentioning
confidence: 97%
“…The above systems showed different behaviors and performances. Indeed, COD removals between 71 and 99.4% were detected while using anaerobic systems, with the AMBR reactors having the highest removal rates reported [36]. Mokhtarani et al [12] found that the COD removal efficiency was independent of organic load rate (OLR) below a value of 6 kg COD /m 3 d, while the COD removal efficiency was significantly reduced above that threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Organic waste, for example, sewage sludge, organic municipal solid waste or green waste, must be stabilized. For this purpose, aerobic stabilization or composting is widely used solution (Roy et al 2018). Both these processes proceed in the same way.…”
Section: Introductionmentioning
confidence: 99%
“…The MBR is usually combined with conventional systems including thermophilic or mesophilic bioprocesses, AOPs, powdered activation carbon to enhance improve the water quality and treatability efficiency [39,40,42,44]. Some of the advantages of MBRs include small foot-print requirement, simple transport configuration and the ability to handle high biomass concentrations [45].…”
Section: Membrane Bioreactorsmentioning
confidence: 99%